2010
DOI: 10.1007/s10546-010-9500-5
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Coherent Turbulence Structures in the Near-Neutral Atmospheric Boundary Layer

Abstract: Turbulence structures of high Reynolds number flow in the near-neutral atmospheric boundary layer (ABL) are investigated based on observations at Shionomisaki and Shigaraki, Japan. A Doppler sodar measured the vertical profiles of winds in the ABL. Using the integral wavelet transform for the time series of surface wind data, the pattern of a descending high-speed structure with large vertical extent (from the surface to more than 200-m level) is depicted from the Doppler sodar data. Essentially this structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
2
19
0
1
Order By: Relevance
“…Such investigations, focusing mainly on the neutral ABL, found turbulent structures similar to laboratory structures, such as hairpins, hairpin packets and cross-stream vortices (which might be the leading edges of hairpin vortices) and large-scale organized motions (e.g. Boppe et al 1999;Horiguchi et al 2010). In addition, recent review articles have compiled studies that indicate that turbulence and the pressure field in the atmospheric surface layer (ASL) scale similarly to canonical wall-bounded flows (Marusic et al 2010a), further suggesting that the coherent structures responsible for this scaling are similar.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Such investigations, focusing mainly on the neutral ABL, found turbulent structures similar to laboratory structures, such as hairpins, hairpin packets and cross-stream vortices (which might be the leading edges of hairpin vortices) and large-scale organized motions (e.g. Boppe et al 1999;Horiguchi et al 2010). In addition, recent review articles have compiled studies that indicate that turbulence and the pressure field in the atmospheric surface layer (ASL) scale similarly to canonical wall-bounded flows (Marusic et al 2010a), further suggesting that the coherent structures responsible for this scaling are similar.…”
mentioning
confidence: 92%
“…Coherent structures have been also investigated in the ABL through numerical simulations, scale model experiments, and field experiments (e.g. Hommema and Adrian 2003;Carper and Porte-Agel 2004;Kanda 2006;Huang et al 2009;Inagaki and Kanda 2010;Horiguchi et al 2010). Such investigations, focusing mainly on the neutral ABL, found turbulent structures similar to laboratory structures, such as hairpins, hairpin packets and cross-stream vortices (which might be the leading edges of hairpin vortices) and large-scale organized motions (e.g.…”
mentioning
confidence: 99%
“…Turbulence structures in such a neutral boundary layer with small buoyancy effects are expected to have different geometric aspects from those in the stable or unstable boundary layer. In the near-neutral ABL, Horiguchi et al (2010) revealed a descending large-scale high-speed structure using a Doppler sodar and sonic anemometer. Although this structure was of large extent in the vertical direction, precise measurements by the sonic anemometer were limited to the surface layer.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong and Hussain 1995). This explains the great attention regarding empirical techniques from the ABL research community where the variable interval time average (VITA) (Kailas and Narasimha 1994) and wavelet methods (Collineau and Brunet 1993;Barthlott et al 2007;Horiguchi et al 2010) have been used extensively. In the special case of flow over a forest canopy, the presence of coherent structures is strongly supported by experimental evidences.…”
Section: Introductionmentioning
confidence: 99%